Perceptions regarding an ‘effective medical teacher’ among undergraduate students of a medical college in Puducherry - Arumugam, Arulkavi; Anandan, Velavan; Purty, Anil J. (International Journal of Research in Medical Sciences, 2021)
Background: To find the characteristics of an effective medical teacher, as perceived by the under graduate medical students who are at different stages of the MBBS course. Methods: A cross sectional study was done among all the undergraduate medical students studying in a medical college and hospital in Puducherry. The undergraduate students were visited in batches and students were explained regarding objectives and those who consented for the study were administered with a validated and pretested questionnaire in line with the objective of the study. The results are expressed in the form of proportions and percentages and the chi-square-test was used to test the significance of difference observed between different batches of student Results: The most important qualities perceived by the students for being an effective medical teacher are creating interest in the subject, having good communication skills, providing good resource material, inspiring and motivating students, being easily approachable, respecting students/ patients / other staff, being enthusiastic, energetic and good listener. There is a significant difference in the perceived importance among different batch of students in the domain of teaching skills of a medical teacher Conclusions: This study identified qualities of medical teachers related to their teaching skills, usage of teaching learning methods, approach towards students and their personal qualities that are perceived to be more important by medical students.